Real‐Time Imaging of Dynamic Cell Reprogramming with Nanosensors. Issue 17 (3rd April 2018) - Wiraja, Christian; Yeo, David C.; Tham, Khek‐Chian; Chew, Sharon W. T.; Lim, Xinhong; Xu, Chenjie
Abstract: Cellular reprogramming, the process by which somatic cells regain pluripotency, is relevant in many disease modeling, therapeutic, and drug discovery applications. Molecular evaluation of reprogramming (e.g., polymerase chain reaction, immunostaining) is typically disruptive, and only provides snapshots of phenotypic traits. Gene reporter constructs facilitate live‐cell evaluation but is labor intensive and may risk insertional mutagenesis during viral transfection. Herein, the utilization of a non‐integrative nanosensor is demonstrated to visualize key reprogramming events in situ within live cells. Principally based on sustained intracellular release of encapsulated molecular probes, nanosensors successfully monitored mesenchymal‐epithelial transition, pluripotency acquisition, and transdifferentiation events. Tracking the dynamic expression of four pivotal biomarkers (i.e., THY1, E‐CADHERIN, OCT4, and GATA4 mRNA), nanosensor signal showed great agreement with polymerase chain reaction and gene reporter imaging ( R 2 > 0.9). Overall, such facile, versatile nanosensor enables real‐time monitoring of low‐frequency reprogramming events, thereby useful for high‐throughput assessment, optimization, and biomarker‐specific cell enrichment. Abstract : Cellular reprogramming has wide relevance in disease modeling, therapeutic, and drug discovery applications . Molecular evaluation methods are typically disruptive, or involve gene reporter modification that risks insertional mutagenesis. To address this, the use of a non‐integrative molecular beacon nanosensor to monitor dynamic key events related to cell reprogramming (mesenchymal‐epithelial transition, acquisition of pluripotency, and transdifferentiation) is described.